Dual targeting of l-carnitine-conjugated nanoparticles to OCTN2 and ATB0,+ to deliver chemotherapeutic agents for colon cancer therapy - Longfa Kou; Qing Yao; Sathish Sivaprakasam; Qiuhua Luo; Yinghua Sun; Qiang Fu; Zhonggui He; Jin Sun; Vadivel Ganapathy (Taylor & Francis Group, 2017)
l-Carnitine, obligatory for oxidation of fatty acids, is transported into cells by the Na+-coupled transporter OCTN2 and the Na+/Cl--coupled transporter ATB0,+. Here we investigated the potential of L-carnitine-conjugated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (LC-PLGA NPs) to deliver chemotherapeutic drugs into cancer cells by targeting the nanoparticles to both OCTN2 and ATB0,+. The cellular uptake of LC-PLGA NPs in the breast cancer cell line MCF7 and the colon cancer cell line Caco-2 was increased compared to unmodified nanoparticles, but decreased in the absence of co-transporting ions (Na+ and/or Cl-) or in the presence of competitive substrates for the two transporters. Studies with fluorescently labeled nanoparticles showed their colocalization with both OCTN2 and ATB0,+, confirming the involvement of both transporters in the cellular uptake of LC-PLGA NPs. As the expression levels of OCTN2 and ATB0,+ are higher in colon cancer cells than in normal colon cells, LC-PLGA NPs can be used to deliver chemotherapeutic drugs selectively into cancer cells for colon cancer therapy. With 5-fluorouracil-loaded LC-PLGA NPs, we were able to demonstrate significant increases in the uptake efficiency and cytotoxicity in colon cancer cells that were positive for OCTN2 and ATB0,+. In a 3D spheroid model of tumor growth, LC-PLGA NPs showed increased uptake and enhanced antitumor efficacy. These findings indicate that dual-targeting LC-PLGA NPs to OCTN2 and ATB0,+ has great potential to deliver chemotherapeutic drugs for colon cancer therapy. Dual targeting LC-PLGA NPs to OCTN2 and ATB0,+ can selectively deliver chemotherapeutics to colon cancer cells where both transporters are overexpressed, preventing targeting to normal cells and thus avoiding off-target side effects.